Continuity and change in Indian grand strategy: The cases of nuclear non-proliferation and climate change - Miller, M; Sullivan de Estrada, K (Routledge, 2018)
This article offers an alternative understanding of India’s post-Cold War grand strategy by arguing that policy issues should be treated as a continuum within which there may be strategic policy innovations, leading to both nuanced continuity and change in foreign policy. Our argument stands in contradistinction to the dominant scholarship in the Indian foreign policy literature, the “transformation scholarship” as we term it, which views policy issues as binary, finds a “new” emphasis on material interests since the end of the Cold War and advocates this as both rational and commendable. Applying four key claims in the dominant transformation scholarship to two important Indian foreign policy issues, nuclear non-proliferation and climate change, we find that, rather than sweeping change in Indian grand strategy, as implied and advocated by transformation scholars, Indian grand strategy is in a state of flux, encapsulating some change but also much continuity.